Macroeconomic Effects of Disruptions in Global Food Commodity Markets: Evidence for the United States - Jasmien de Winne; Gert Peersman (Center for Economic Studies and ifo Institute (CESifo), 2016)
We use two approaches to examine the macroeconomic consequences of disruptions in global food commodity markets. First, we embed a novel quarterly composite global production index for the four basic staples (corn, wheat, rice and soybeans) in a standard vector autoregression (VAR) model, and we estimate the dynamic effects of global food commodity supply shocks on the US economy. As an alternative, we also estimate the consequences of thirteen narratively identified global food commodity price shocks. Both approaches deliver similar conclusions. Specifically, an unfavorable food commodity market shock raises food commodity prices, and leads to a rise in food, energy and core inflation, and to a persistent fall in real GDP and consumer expenditures. A closer inspection of the pass-through reveals that households do not only reduce food consumption. In fact, there is a much greater decline in durable consumption and investment. Overall, the macroeconomic effects turn out to be a multiple of the maximum impact implied by the share of food commodities in the consumer price index and household consumption.
Keywords: E30; 330; food commodity prices; food production; macro effects